2010
DOI: 10.1039/b916663g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ternary CuInS2/ZnS quantum dot bioconjugates and their applications for targeted cancer bioimaging

Abstract: This contribution introduces the use of cadmium-free CuInS(2) quantum dots (QDs) for targeted and multiplexed optical imaging of tumors in mice. CuInS(2)/ZnS QDs were synthesized in a non-aqueous phase using the hot colloidal synthesis method. Previous challenges involving stable aqueous dispersion of highly luminescent CuInS(2)/ZnS QDs have been overcome by encapsulating them within functionalized phospholipid micelles, which also facilitated their conjugation with folic acid for targeted delivery. Luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
104
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 49 publications
1
104
1
2
Order By: Relevance
“…Among many candidates, much attention by scientists has been devoted to the ternary quantum dots (QDs) belonging to the A I B III X VI group where A = (Cu, Ag), B = (In, Al, Ga) and X = (S, Se, Te). [1][2][3][4] This is mainly due to their cadmium-free chemical composition and favourable spectroscopic properties in both the energy and time domains which are well matched with those expected for the next generation probes. Due to the size effect, the emission band maximum of the A It is known that metal-enhanced fluorescence or Förster energy transfers shorten the luminescence lifetime making the analysis very challenging for luminescent agents characterized by lifetimes shorter than 30 ns.…”
Section: Introductionmentioning
confidence: 64%
“…Among many candidates, much attention by scientists has been devoted to the ternary quantum dots (QDs) belonging to the A I B III X VI group where A = (Cu, Ag), B = (In, Al, Ga) and X = (S, Se, Te). [1][2][3][4] This is mainly due to their cadmium-free chemical composition and favourable spectroscopic properties in both the energy and time domains which are well matched with those expected for the next generation probes. Due to the size effect, the emission band maximum of the A It is known that metal-enhanced fluorescence or Förster energy transfers shorten the luminescence lifetime making the analysis very challenging for luminescent agents characterized by lifetimes shorter than 30 ns.…”
Section: Introductionmentioning
confidence: 64%
“…Typically, the NP-containing assemblies are produced using microball-like polymer macromolecules capable of binding to the NP surface (for example polyethylene glycol [3,5,6,[9][10][11], phospholipids [12,13], various block-copolymers, DNAs, etc. [3,5]).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer biomarkers such as prostate-specific antigen [36], HER2 [37], CD44 [38], and folic acid [39] specifically present in the tumor microenvironment or on the cancer cells surface, can be recognized by the appropriate monoclonal antibody [40], peptide [41], or immunoglobulin [18,42] that are conjugated onto the QDs surface ( Figure 4). In some circumstances, it has been shown that QDs encapsulated in magnetic liposomes covered by Arginyl-Glycyl-Aspartic acid (RGD) ligands have been utilized for the MRI imaging of tumor angiogenesis [43].…”
Section: Qds As Contrast Agents For Optical Imagingmentioning
confidence: 99%